Arabidopsis Plants Sense Non-self Peptides to Promote Resistance Against Plectosphaerella cucumerina - Pastor-Fernández, Julia; Gamir, Jordi; Pastor, Victoria; Sanchez-Bel, Paloma; Sanmartín, Neus; Cerezo, Miguel; Flors, Víctor (Frontiers in Plant Science, 2020)
Peptides are important regulators that participate in the modulation of almost every physiological event in plants, including defence. Recently, many of these peptides have been described as defence elicitors, termed phytocytokines, that are released upon pest or pathogen attack, triggering an amplification of plant defences. However, little is known about peptides sensing and inducing resistance activities in heterologous plants. In the present study, exogenous peptides from solanaceous species, Systemins and HypSys, are sensed and induce resistance to the necrotrophic fungus Plectospharella cucumerina in the taxonomically distant species Arabidopsis thaliana. Surprisingly, other peptides from closer taxonomic clades have very little or no effect on plant protection. In vitro bioassays showed that the studied peptides do not have direct antifungal activities, suggesting that they protect the plant through the promotion of the plant immune system. Interestingly, tomato Systemin was able to induce resistance at very low concentrations (0.1 nM and 1 nM). Here, we show evidence of the possible involvement of defence-related phytohormones in Systemin-induced resistance (Sys-IR) in Arabidopsis. Systemin itself induced the accumulation of both the Jasmonic acid (JA) and Salicylic acid (SA) hormones, and JA- and SA-dependent gene expression were also increased after infection. An analytical method to identify and quantify peptides by high-performance liquid chromatography (HPLC) coupled to mass spectrometry (MS) was implemented in subsequent quantitative studies.